Follow-up observations at 16 and 33 GHz of extragalactic sources from WMAP 3-yr data: I – Spectral properties - Davies, M.; Franzen, Thomas; Davies, R.; Davis, R.; Feroz, F.; Genova-Santos, R.; Grainge, K.; Green, D.; Hobson, M.; Hurley-Walker, Natasha; Lasenby, A.; Lopez-Caniego, M.; et al. (Oxford University Press, 2009)
We present follow-up observations of 97 point sources from the Wilkinson MicrowaveAnisotropy Probe (WMAP) 3-yr data, contained within the New Extragalactic WMAP PointSource catalogue between-4? =d =60?; the sources form a flux-density-limited sample completeto 1.1 Jy (˜5s) at 33 GHz. Our observations were made at 16 GHz using the ArcminuteMicrokelvin Imager and at 33 GHz with the Very Small Array (VSA).94 of the sources have reliable, simultaneous – typically a few minutes apart – observationswith both telescopes. The spectra between 13.9 and 33.75 GHz are very different from thoseof bright sources at low frequency: 44 per cent have rising spectra (a33.7513.9 < 0.0), where S ??-a, and 93 per cent have spectra with a33.7513.9 < 0.5; the median spectral index is 0.04.For the brighter sources, the agreement between VSA and WMAP 33-GHz flux densitiesaveraged over sources is very good. However, for the fainter sources, the VSA tends to measurelower values for the flux densities than WMAP. We suggest that the main cause of this effectis the Eddington bias arising from variability.